PENGARUH FASILITAS BELAJAR TERHADAP MOTIVASI BELAJAR TARUNA POLTEKIP TINGKAT II PRODI MANAJEMEN PEMASYARAKATAN - M Fahrul Rozi (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The purpose of this study was to determine the effect of learning facilities on the learning motivation of second-level POLTEKIP cadets in correctional management study programs. In this study, the population taken by all cadets of the second level polytechnic study programs of prison management totaling 101 cadets. This study uses Slovin sampling with 81 cadets. The sampling technique uses a simple random sample. The variables in this study are independent, namely Learning Facilities (X) and the dependent variable bound to Learning Motivation (Y). Data analysis applies validity tests, formative tests, and simple linear regression analysis. So it can be concluded that the learning facilities have a significant effect on the learning motivation of second-level polytechnic cadets in the Correctional Management Study Program. The data obtained shows that there is a 71.5% significant influence on learning motivation. At the same time, the remaining 28.5% influenced by several other factors.